The Safety of Soy Leghemoglobin Protein Preparation Derived from Pichia pastoris Expressing a Soy Leghemoglobin Gene from Glycine max: In Vitro and In Vivo Studies - Teresa F. Reyes; Puja Agrawal; Teresa Chan; Richard Green; Ray A. Matulka (Journal of Toxicology, 2023)
Soy leghemoglobin (LegH) protein derived from soy (Glycine max) produced in Pichia pastoris (reclassified as Komagataella phaffii) as LegH Prep is a novel food ingredient that provides meat-like flavor and aroma to plant-derived food products. The safety of LegH Prep has been previously assessed in a battery of in vivo and in vitro testing and found no adverse effects under the conditions tested. In this new work, we present the results of new in vivo and in vitro tests evaluating the safety of LegH Prep. LegH Prep was nonmutagenic in a bacterial reverse mutation assay and nonclastogenic in an in vitro micronucleus assay in human lymphocytes. Systemic toxicity was evaluated in the 90 day dietary study in male and female Sprague–Dawley® rats that included a 28 day recovery period. The study resulted in no animal deaths associated with the administration of LegH Prep at the highest dose (90,000 ppm). There were no significant adverse clinical or physical changes attributed to LegH Prep administration, and no observed adverse effects on either male or female rats over the course of the 28 day recovery phase study. The new 90 day dietary toxicity study established a no observed adverse effect level (NOAEL) of 4798.3 and 5761.5 mg/kg/day, the maximum level tested for male and female rats, respectively. Thus, the results of the studies demonstrate that under the conditions tested, LegH Prep is not toxic for consumption in meat analog products.